The Role Of Interpersonal Communication Between Parents And Children In Building Children's Learning Motivation In Medan Tungungan District - Zahra Ramadhan; Hijrah Hayani; Lily Siti Nurhasna; Yasmin Dhea Fernanda; Roby Septian Nasution; Nursapia Harahap (Jurnal Sosial Sains dan Komunikasi, 2024)
This study aims to analyze the role of interpersonal communication between parents and children in foster-ing children's learning motivation in Medan Tuntungan District. Interpersonal communication is considered a crucial element in supporting children's educational success through openness, empathy, supportive atti-tudes, positive feelings, and supervision. This research employs a qualitative method with in-depth interviews, observations, and document analysis to explore com-munication dynamics within families. The findings re-veal that parents who apply effective interpersonal communication tend to successfully enhance their chil-dren's learning motivation. Factors such as rewards, clear study structures, and limiting technology use are key aspects supporting this success. However, chal-lenges such as technological distractions and authori-tarian communication approaches remain obstacles that need to be addressed. This study offers practical contributions for parents, educators, and policymakers to understand the importance of interpersonal commu-nication in supporting children's education.